Host specificity driving genetic structure and diversity in ectoparasite populations: Coevolutionary patterns in Apodemus mice and their lice - Martinů, Jana; Hypša, Václav; Štefka, Jan (Ecology and evolution, 2018)
A degree of host specificity, manifested by the processes of host-parasite cospeciations and host switches, is assumed to be a major determinant of parasites' evolution. To understand these patterns and formulate appropriate ecological hypotheses, we need better insight into the coevolutionary processes at the intraspecific level, including the maintenance of genetic diversity and population structure of parasites and their hosts. Here, we address these questions by analyzing large-scale molecular data on the louse Polyplax serrata and its hosts, mice of the genus Apodemus, across a broad range of European localities. Using mitochondrial DNA sequences and microsatellite data, we demonstrate the general genetic correspondence of the Apodemus/Polyplax system to the scenario of the postglacial recolonization of Europe, but we also show several striking discrepancies. Among the most interesting are the evolution of different degrees of host specificity in closely related louse lineages in sympatry, or decoupled population structures of the host and parasites in central Europe. We also find strong support for the prediction that parasites with narrower host specificity possess a lower level of genetic diversity and a deeper pattern of interpopulation structure as a result of limited dispersal and smaller effective population size.
Keywords: coevolution; genetic diversity; Apodemus; Polyplax; host specificity; dispersal